Chemokine GPCR signaling inhibits β-catenin during zebrafish axis formation. - Shu-Yu Wu; Jimann Shin; Diane S Sepich; Lilianna Solnica-Krezel (PLoS Biology)
Embryonic axis formation in vertebrates is initiated by the establishment of the dorsal Nieuwkoop blastula organizer, marked by the nuclear accumulation of maternal β-catenin, a transcriptional effector of canonical Wnt signaling. Known regulators of axis specification include the canonical Wnt pathway components that positively or negatively affect β-catenin. An involvement of G-protein coupled receptors (GPCRs) was hypothesized from experiments implicating G proteins and intracellular calcium in axis formation, but such GPCRs have not been identified. Mobilization of intracellular Ca(2+) stores generates Ca(2+) transients in the superficial blastomeres of zebrafish blastulae when the nuclear accumulation of maternal β-catenin marks the formation of the Nieuwkoop organizer. Moreover, intracellular Ca(2+) downstream of non-canonical Wnt ligands was proposed to inhibit β-catenin and axis formation, but mechanisms remain unclear. Here we report a novel function of Ccr7 GPCR and its chemokine ligand Ccl19.1, previously implicated in chemotaxis and other responses of dendritic cells in mammals, as negative regulators of β-catenin and axis formation in zebrafish. We show that interference with the maternally and ubiquitously expressed zebrafish Ccr7 or Ccl19.1 expands the blastula organizer and the dorsoanterior tissues at the expense of the ventroposterior ones. Conversely, Ccr7 or Ccl19.1 overexpression limits axis formation. Epistatic analyses demonstrate that Ccr7 acts downstream of Ccl19.1 ligand and upstream of β-catenin transcriptional targets. Moreover, Ccl19/Ccr7 signaling reduces the level and nuclear accumulation of maternal β-catenin and its axis-inducing activity and can also inhibit the Gsk3β -insensitive form of β-catenin. Mutational and pharmacologic experiments reveal that Ccr7 functions during axis formation as a GPCR to inhibit β-catenin, likely by promoting Ca(2+) transients throughout the blastula. Our study delineates a novel negative, Gsk3β-independent control mechanism of β-catenin and implicates Ccr7 as a long-hypothesized GPCR regulating vertebrate axis formation.